Research on Meshing Principle and Active Design Method of Uniform-variable Gear Drive - Jian Wang; Jianming Fan; Yong Feng (Jixie chuandong)
In paper-transferring mechanism with variable speeds and textile machines，the driven gear are required to output multifarious motions when the driving gear rotates for 1 cycle. A new gear drive，called uniform-variable gear is proposed. The notion of the uniform-variable gear refers to non-circular gears where the driven gear can bring about uniform，accelerated and decelerated motion during rotation，whilst the driving gear itself rotates at a constant speed. The active design method of this new gear drive is researched. According to the characteristics of smooth curve and closed pitch curve，the mathematical models of pitch curves are derived based on given motion feature of the driven gear. The pitch curves of I-type and II-type uniform-variable gears are built through the design of example drives. The assembly models of uniform-variable gears are given by using the software of Croe. By using the software of Adams, the motion simulation of the gear is carried out, the simulation results are basically consistent with the given curve shape. The results show that, by changing the angular velocity and angular acceleration curves of the driven gear, the pitch curves of the uniform-variable gear can be directly and effectively controlled.